2007
DOI: 10.1111/j.1468-8123.2007.00168.x
|View full text |Cite
|
Sign up to set email alerts
|

Wettability alteration of caprock minerals by carbon dioxide

Abstract: One of the critical factors that control the efficiency of CO 2 geological storage process in aquifers and hydrocarbon reservoirs is the capillary-sealing potential of the caprock. This potential can be expressed in terms of the maximum reservoir overpressure that the brine-saturated caprock can sustain, i.e. of the CO 2 capillary entry pressure. It is controlled by the brine/CO 2 interfacial tension, the water-wettability of caprock minerals, and the pore size distribution within the caprock.By means of conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

37
375
3
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 435 publications
(431 citation statements)
references
References 31 publications
(98 reference statements)
37
375
3
1
Order By: Relevance
“…Figure 2a. Results show that the advancing contact angle is considerably higher than the receding contact angle in the same pore throat, consistent with previous studies [18,22,[43][44][45]. The difference between ACA and RCA is attributed to the blemishes on non-ideal surfaces which results in pinning the interfaces to the solid surface [46].…”
Section: Contact Angle Measurementsupporting
confidence: 80%
See 4 more Smart Citations
“…Figure 2a. Results show that the advancing contact angle is considerably higher than the receding contact angle in the same pore throat, consistent with previous studies [18,22,[43][44][45]. The difference between ACA and RCA is attributed to the blemishes on non-ideal surfaces which results in pinning the interfaces to the solid surface [46].…”
Section: Contact Angle Measurementsupporting
confidence: 80%
“…Average contact angles on flat surface inside micromodel at pressure of one and eight megapascals are 62° ± 7° and 49° ± 21°, respectively, in agreement with Kim et al [58] observations showing a wide range of contact angles from 40° to 80° inside a uniform micromodel. Contact angles on a flat surface in this study are higher than those shown in previous sessile drop or captive bubble tests with large droplet of water or bubble of CO2 (i.e., 8° to 45° on silica or glass surface) [18,22,43,[50][51][52]. This could be due to the micro-scaled CO2 bubble size on a flat surface inside the micromodel of [18,22,43,[50][51][52].…”
Section: Comparing Contact Angle Of Bubbles On Flat Surface With Contcontrasting
confidence: 51%
See 3 more Smart Citations